Şeyh Fâris el-Hûrî’nin Kenz-i Lugât adlı eseri ve eserdeki söz yapımı - Faidhallah, Faisal Abdulrashid M. (My University, 2020)
ÖZETDeyrü’l-Kamer kasabasında bulunan Azîziyye medresesinde Türkçe öğretmenliği yapan Şeyh Fâris Efendi El-Hûrî’nin 1874’de yazdığı Kenz-i Lugât adlı eser, 1876 senesinde basılmıştır. Bu sözlükten önce Hûrî, Reşedetü’t-Tullâb adlı bir gramer kitabı yazmıştır.Teze konu olan Kenz-i Lugât adlı eserin üzerinde yaptığımız çalışma giriş, inceleme, metin, dizin, tıpkıbasım olmak üzere beş ana bölümünden oluşmaktadır. Giriş bölümünde yazarın hayatı, eserleri ve üzerinde çalıştığımız eserin üzerinde durulmuştur. İnceleme bölümü transkripsiyon metni, yabancılara Türkçe öğretimi ve söz yapımı olmak üzere üç bölümden oluşmaktadır. Metin bölümünde Kenz-i Lugât’in söz varlığı kitabın orijinalinde olduğu gibi dört sütun hâlinde düzenlenmiş, sözcüklerin çevriyazısı, Arap harfli yazılışı, Arapça karşılığı ve Arapça karşılığın Türkçe çevirisi verilmiştir. Dizin bölümü iki kısımdan oluşmaktadır: Latin harfli alfabetik dizin, Arap harfli dizin. Tıpkıbasım bölümünde eserin tamamının fotoğrafları yer almaktadır.

ABSTRACTKenz-i Lugât that was written in 1874 by Sheyh Fâris Efendi who was a teacher in Aziziye medrese located in Deyrü’l-kamer, was published in 1876. The reason of writing this dictionary was not having any Turkish-Arabic dictionaries for Arabs in those days. Before this dictionary Hûrî also wrote a grammar book named Reshedetul Tullab.The research we have made about the subject of the thesis Kenz-i Lugât is about five parts and these parts are introduction, examination, the text, the directory and facsimile. At the introduction part we mentioned about the author’s life, his works and the dictionary we researched. The examination part is about three sections which are transcription text, teaching Turkish to foreigners and the word making. At the text part we’ve worked on, the vocabulary of kenz-i Lugât prepared in four columns just like in it’s original, the translation of words, their spellings in Arabic letters, their Arabic counterparts and the Turkish translation of the Arabic counterparts. The directory is about two sections : The alphabetic directory in Latin letters, the directory in Arabic letters. In the facsimile section there can be found the complete pictures of the dictionary
Keywords: dictionary; History and criticism; Kenz-i Lugât; Söz yapımı; Sözlük Sheyh Fâris El-Hûrî; Şeyh Fâris El-Hûrî; Tarih ve eleştiri; Turkish literature; Türk edebiyatı; word making